2020
DOI: 10.3390/jcm9092794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in the Condylar Volume and Morphology in Skeletal Class III Deformities Undergoing Orthognathic Surgery Using a Customized versus Conventional Miniplate: A Retrospective Analysis

Abstract: With the great leap in the development of three-dimensional computer-assisted surgical technology, surgeons can use a variety of assistive methods to achieve better results and evaluate surgical outcomes in detail. This retrospective study aimed to evaluate the postoperative stability after bilateral sagittal split ramus osteotomy by volume rendering methods and to evaluate how postoperative stability differs depending on the type of surgical plate. Of the patients who underwent BSSRO, ten patients in each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In the present study, a single examiner performed the volumetric analysis of the mandibular condyles. The single examiner concept was used by da Silva et al, Kim et al, and Lim et al 11 , 13 , 14 In the present study, the intra-examiner reliability was 0.93. Studies have reported excellent intra-examiner reliability for volumetric assessment of condyles using CBCT.…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, a single examiner performed the volumetric analysis of the mandibular condyles. The single examiner concept was used by da Silva et al, Kim et al, and Lim et al 11 , 13 , 14 In the present study, the intra-examiner reliability was 0.93. Studies have reported excellent intra-examiner reliability for volumetric assessment of condyles using CBCT.…”
Section: Discussionsupporting
confidence: 50%
“…This study was conducted to investigate changes in temporomandibular joint space after IVRO. Recent studies have combined patients who underwent LeFort I osteotomies with those who did not 30 32 . However, since this may affect the results, future research is needed to distinguish between these patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…This task requires excellent precision and expertise. Nonetheless, recent advancements in patient-specific plates (PSPs) have improved the accuracy of condyle repositioning [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%